The Interplay Between the DNA Damage Response, RNA Processing and Extracellular Vesicles - Meng, Xiangbing; Yang, Shujie; Camp, Vanessa J. A. (Frontiers in Oncology, 2020)
RNA processing was recently found to affect DNA damage response. The RNA processing factors THRAP3 and BCLAF1 play critical role in keeping DNA genomic stability by regulating the transcription, mRNA splicing and export of DNA repair proteins BRCA2, PALB2, Rad51, FANCD2 and FANCL in response to DNA damage. RNA processing factors THRAP3 and BCLAF1 play critical roles in maintaining DNA genomic stability. These factors regulate transcription, mRNA splicing and nuclear RNA export of DNA repair proteins BRCA2, PALB2, Rad51, FANCD2 and FANCL in response to DNA damage. Splicing factors SRSF10 and Sam68 were found to control the DNA damage agent-induced mRNA splicing of transcripts including BCLAF1, BRCA1, BCL2L1, CASP8, CHK2 and RBBP8 to regulate apoptosis, cell-cycle transition and DNA repair. Splicing factors and RNA binding proteins (RBPs) were also found to play a critical role in DNA/RNA hybrids (R-loops) formed during transcription and RNA processing to prevent RNA-induced genome instability. At the same time, DNA repair proteins FANCI and FANCD2 were found to regulate the nuclear localization of splicing factors SF3B1 in the DNA damage response. In addition, tumor-derived extracellular vesicles (Evs) enhanced by chemotherapeutic agents in cancer were found to promote cancer metastasis and drug resistance. Inhibiting Evs from cancer cells significantly reduced cancer metastasis and drug resistance. Furthermore, cross-talk between the DNA damage response and the immune response was observed including the enhancement of the efficacy of immune checkpoint blockade by PARP inhibitors and the effect of PD-L1 on mRNA stability of various mRNAs involved in DNA damage response by acting as a novel RNA binding protein to increase drug resistance in cancer cells. This review will introduce recent progress on the interplay of the DNA damage response, the RNA processing and the extracellular vesicles mediated metastasis.